Organophosphate and carbamate insecticide exposure is related to lung function change among smallholder farmers: a prospective study. Issue 8 (21st January 2021) - Hansen, Martin Rune Hassan; Jørs, Erik; Sandbæk, Annelli; Sekabojja, Daniel; Ssempebwa, John C; Mubeezi, Ruth; Staudacher, Philipp; Fuhrimann, Samuel; Sigsgaard, Torben; Burdorf, Alex; Bibby, Bo Martin; Schlünssen, Vivi
Abstract : Introduction and aim: Exposure to some insecticides may cause airway obstruction, but existing evidence is limited by cross-sectional designs and inadequate confounder control. We investigated the relation between organophosphate and carbamate insecticides and pulmonary function in a prospective study accounting for important confounders. Methods: In a cohort of 364 smallholder farmers in Uganda (69% women), participants underwent pre-bronchodilator spirometry at baseline (September/October 2018) and at two follow-up visits (November/December 2018 and January/February 2019). Exposure to carbamate and organophosphate insecticides was assessed using haemoglobin-adjusted erythrocyte acetylcholinesterase (AChE/Hb). Less than 3% of participants were lost to follow-up. We calculated Z-scores for FEV1, FVC and FEV1 /FVC using the Global Lung Function Initiative equations. Data were analysed in linear mixed and fixed effect models accounting for family relationships and repeated measures of exposure and outcome. Results: Low AChE/Hb was significantly associated with low FEV1 Z-score in both unadjusted and adjusted analyses. Compared with individuals with AChE/Hb 25.90 U/g (50 th percentile, reference), those with lower AChE/Hb 24.50 U/g (35 th percentile) had mean FEV1 Z-score 0.045 (0.003 to 0.087) lower, and persons with higher AChE/Hb 27.30 U/g (65 th percentile) had a mean FEV1 Z-score 0.043 (−0.002 to 0.087) higher compared with the reference. Similar, but numerically smaller and statistically non-significant effects were seen for Z-scores of FVC and FEV1 /FVC. Conclusion: Exposure to organophosphate and carbamate insecticides may lead to lung function decline. Our results add to the growing evidence of health effects in relation to exposure to organophosphate and carbamate insecticides, underlining the importance of minimising exposure.